On the introduction of return window to supply chains with online channel. (October 2022) - Pi, Zhenyang; Fang, Weiguo; Zhao, Qiuhong; Zhang, Baofeng
Highlights: Return window is introduced to the supply chain with online channel. Pricing and channel strategies are derived in centralized and decentralized systems. The return window is longer in a centralized system than in a decentralized one. Introducing return window limits the supplier to choose a dual-channel strategy. Abstract: In the E-commerce era, many firms offer return policy in the form of return window, allowing consumers to return for a full refund within a specific time, which has an important effect on supply chain operations. Motivated by practical observations, we explore a supplier's distribution channel strategy when introducing return window in both centralized and decentralized supply chain systems. A game-analytical model is developed to study the interaction between channel strategy and return window. The equilibrium channel strategies, return windows, and prices in the two systems are derived. We find that a long return window always tends to be offered by the supplier when the direct channel is open (in a dual-channel or single direct-channel strategy) since it expands potential market demand. Also, the supplier provides a shorter return window in the decentralized than the centralized system as the existence of double marginalization, which enriches existing results. We prove that introducing return window always restricts the supplier to choose a dual-channel strategy, but it incentivizes (restricts) the supplier to choose a single retail-channel strategy in the decentralized (centralized) system in response to changing cost pressures. Our theoretical findings provide insights for managing supply chains when introducing return window as a market strategy.